Four luminescent metal-organic chain compounds based on semi-rigid N-donor ligands and 3-hydroxy-2-naphthoic acid for recognition of Fe3+ and Cr2O72− ions. (15th March 2020) - Wang, Xiang; Xiao, Hanyu; Zhang, Mingze; Lin, Hongyan; Liu, Guocheng
Graphical abstract: Four luminescent complexes based on semi-rigid N -donor ligands and 3-hydroxy-2-naphthoic acid show outstanding luminescent detection capabilities against Fe 3+ and Cr2 O7 2− ions in DMF with excellent selectivity and sensitivity. Highlights: Four complexes based on N -donor ligands and 3-hydroxy-2-naphthoic acid were prepared. All of them have 1D chain structures. They display excellent luminescent detection capabilities for Fe 3+ and Cr2 O7 2− ions. Abstract: Four luminescent metal-organic complexes based on semi-rigid N -donor ligands and 3-hydroxy-2-naphthoic acid (3-HNA), [Zn(bimb)(3-HNA)2 ] (1 ), [Zn(bbimb)(3-HNA)2 ]·3H2 O (2 ), [Zn(bimbp)(3-HNA)2 ] (3 ), [Cd(bimbp)(3-HNA)2 ] (4 ) [bimb = 1, 4-bis(1-imidazol-yl-methyl)benzene, bimbp = 4, 4′-bis(1H-imidazol-1-yl-methyl)biphenyl, bbimb = 1, 4-bis(1-benzimidazolyl-yl-methyl)benzene], have been synthesized solvothermally. The 1D chain structures of complexes 1 –4 exhibit the Z-type or linear geometry configurations, where the combination of the N -donor ligands and transition metal ions is regarded as the backbones, and the 3-HNA ligands are dangled covalently on both sides of such backbone. The investigation on the luminescence properties indicates that complexes 1 –4 have luminescent detection capabilities against Fe 3+ and Cr2 O7 2− ions in DMF with excellent selectivity and sensitivity.